MCA MICROSOFT CERTIFIED ASSOCIATE AZURE NETWORK ENGINEER STUDY GUIDE exam az-700 - Udayakumar, Puthiyavan (WILEY-SYBEX, 2022)
Prepare to take the NEW Exam AZ-700 with confidence and launch your career as an Azure Network Engineer Not only does MCA Microsoft Certified Associate Azure Network Engineer Study Guide: Exam AZ-700 help you prepare for your certification exam, it takes a deep dive into the role and responsibilities of an Azure Network Engineer, so you can learn what to expect in your new career. You'll also have access to additional online study tools, including hundreds of bonus practice exam questions, electronic flashcards, and a searchable glossary of important terms. Prepare smarter with Sybex's superior interactive online learning environment and test bank. Exam AZ-700, Designing and Implementing Microsoft Azure Networking Solutions, measures your ability to design, implement, manage, secure, and monitor technical tasks such as hybrid networking; core networking infrastructure; routing; networks; and private access to Azure services. With this in-demand certification, you can qualify for jobs as an Azure Network Engineer, where you will work with solution architects, cloud administrators, security engineers, application developers, and DevOps engineers to deliver Azure solutions. This study guide covers 100% of the objectives and all key concepts, including: Design, Implement, and Manage Hybrid Networking Design and Implement Core Networking Infrastructure Design and Implement Routing Secure and Monitor Networks Design and Implement Private Access to Azure Services If you're ready to become the go-to person for recommending, planning, and implementing Azure networking solutions, you'll need certification with Exam AZ-700. This is your one-stop study guide to feel confident and prepared on test day. Trust the proven Sybex self-study approach to validate your skills and to help you achieve your career goals!.